Defined media for optimal pyoverdine production by Pseudomonas fluorescens 2-79 - Kisaalita, William S.; Slininger, Patricia J.; Bothast, Rodney J. (Applied microbiology and biotechnology, 1993)
Pseudomonas fluorescens strain 2-79 (NRRL-15132) produces a fluorescent yellow-green pyoverdine when cultured on Fe(III)-poor medium. When cultured on Fe(III)-rich medium, strain 2-79 produces an antibiotic, phenazine 1-carboxylic acid, which is effective in suppressing plant fungal diseases such as take-all of wheat. A 23 factorial design was used to examine pyoverdine production as a function of the presence or absence of Bacto casamino acids, purines-pyrimidines and vitamins in an iron-deficient medium. Amino acids were found to be an important factor (P=0.0002). A Plackett-Burman design was used to identity eight amino acids, out of the 19 present in casamino acids, that were responsible for the increased pyoverdine production: methionine, valine, isoleucine, tyrosine, proline, phenylalanine, glutamic acid, and glycine. Biomass was enhanced only by glutamic acid.